Growth of Kappaphycus alvarezii seaweed in off-bottom technique with different number of cultivation facilities - Aripin, Aripin; Muzahar, Muzahar; Irawan, Henky (Universitas Malikussaleh, 2025)
Seaweed or algae is macro algae whose habitat is in sea water and several types in brackish water. There are several seaweed cultivation techniques, one of which is the off-bottom technique. The off-bottom technique with different levels of cultivation facilities where seaweed seeds are placed has never been carried out by aquaculturis in the Bintan Island area, Riau Islands (Kepri). The aim of the research was to determine the speed of increase in weight of seaweed grown in cultivation facilities with different numbers of levels using the off-bottom technique. The research will be carried out in September-October 2022 on the sea coast of Tembeling Village, Bintan Regency. The experiment was carried out with three treatments and each was repeated 3 times in a completely randomized design. The treatments consisted of 1 level (K), 2 levels (A) and 3 levels (B) cultivation facilities. The Anova results showed that the weight gain of the seaweed test was significantly different between the three treatments (p<0.05). The best results in the 3 level cultivation facility treatment (B) were 11.04±0.73 g, but the survival and daily growth rates were not significantly different (p>0.05). Keywords: Off-Bottom Technique; Number of Different Levels of Cultivation Facilities